Effect of dose and source of potassium on yield and quality of ’Alphonso Mangao (Mangifera indica) - SHINDE, A K; DABKE, D J; JADHAV, B B; KANDALKAR, MP; BURONDKAR, M M (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2001-2003 to study the effect of different doses and sources ofpotassium on yield and quality of ’Alphonso’ mango (Mangifera indica L.) at the Central Experimental Station, Wakavali, Maharashtra. The pooled results of this experimentation revealed a new recommendation to mango growers as soil application of 50 kg farmyard manure, 1.5 kg N, 0.5 kg P20S and 1.0 kg K20 in the form of sulphate of potassiunm tree in the first fortnight of June and application of paclobutrazol @O.75g a i/m canopy diameter during second fortnight of July to first fortnight of August with 3 foliar sprays of 1% KN03 at peanut, marble and egg stage to increase yield and quality of ’Alphonso’ mango. This treatment increased the flowering (11.89%), fruit retention (34.28%), fruit yield (28.93%), fruit weight (5.15%), ascorbic acid (26.99%), organoleptic score for texture, flavour, colour and shelf-life and reduced physiological weight loss (22.79%) and spongy tissue (68.08%) over the previous recommendation of soil application of 50 kg farm yard manure, 1.5 kg N, 0.5 kg P20S and 0.5 kg K20/tree during August.